FRB microstructure revealed by the real-time detection of FRB170827. Issue 1 (3rd May 2018) - Farah, W; Flynn, C; Bailes, M; Jameson, A; Bannister, K W; Barr, E D; Bateman, T; Bhandari, S; Caleb, M; Campbell-Wilson, D; Chang, S-W; Deller, A; et al.
Abstract: We report a new fast radio burst (FRB) discovered in real-time as part of the UTMOST project at the Molonglo Observatory Synthesis Radio Telescope. FRB170827 was first detected with our low-latency (<24 s) and machine-learning based FRB detection system. The FRB discovery was accompanied by the capture of voltage data at the native time and frequency resolution of the observing system, enabling coherent dedispersion and detailed off-line analysis that have unveiled fine temporal and frequency structure. The dispersion measure (DM) of 176.80 ± 0.04 pc cm −3 is the lowest of the FRB population. The Milky Way contribution along the line of sight is ∼40 pc cm −3, leaving an excess DM of ∼145 pc cm −3 . The FRB has a fluence >20 ± 7 Jy ms, and is narrow with a width of ∼400 s at 10 per cent of its maximum amplitude. However, the burst shows three temporal components, the narrowest of which is ∼30 s, and a scattering time-scale of 4.1 ± 2.7 s. The FRB shows spectral modulations on frequency scales of 1.5 MHz and 0.1 MHz. Both are prominent in the dynamic spectrum, which shows a very bright region of emission between 841 and 843 MHz, and weaker and patchy emission across the entire band. We show that the fine spectral structure could arise in the FRB host galaxy, or its immediate vicinity.